2014
DOI: 10.1007/s00395-014-0409-x
|View full text |Cite
|
Sign up to set email alerts
|

The role of capillary transit time heterogeneity in myocardial oxygenation and ischemic heart disease

Abstract: Ischemic heart disease (IHD) is characterized by an imbalance between oxygen supply and demand, most frequently caused by coronary artery disease (CAD) that reduces myocardial perfusion. In some patients, IHD is ascribed to microvascular dysfunction (MVD): microcirculatory disturbances that reduce myocardial perfusion at the level of myocardial pre-arterioles and arterioles. In a minority of cases, chest pain and reductions in myocardial flow reserve may even occur in patients without any other demonstrable sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 113 publications
2
55
0
1
Order By: Relevance
“…1D-b). Given that MI induces a shortage in the oxygen supply to the cardiomyocytes [14,34], we examined the effect of hypoxia on Siat7A expression in vitro. Real-time PCR and immunoblotting as well as confocal microscopy analysis were performed using the cultured human cardiomyocyte cell line, AC16 (Fig.…”
Section: Siat7a Expression Was Increased In Damaged Cardiomyocytes Afmentioning
confidence: 99%
“…1D-b). Given that MI induces a shortage in the oxygen supply to the cardiomyocytes [14,34], we examined the effect of hypoxia on Siat7A expression in vitro. Real-time PCR and immunoblotting as well as confocal microscopy analysis were performed using the cultured human cardiomyocyte cell line, AC16 (Fig.…”
Section: Siat7a Expression Was Increased In Damaged Cardiomyocytes Afmentioning
confidence: 99%
“…Several studies have reported an increased level of plasma EPO in patients with heart failure, which was correlated to a more severe outcome [10][11][12][13]. Meanwhile, female gender, inflammation, hyperphosphatemia, hyperglycemia, and dyslipidemia were identified as potential risk factors of microvascular dysfunction [14][15][16]. In postmenopausal women, microvascular dysfunction has been linked with adverse outcomes, such as Syndrome X [14].…”
Section: Discussionmentioning
confidence: 99%
“…The first is that the reticulocyte count could be a sensitive marker of tissue hypoxia. Reductions in tissue oxygen tension due to microvascular dysfunction would be expected to lead to the activation of hypoxia-inducible transcription factors [15], which in turn might initiate the production of EPO. EPO increases reticulocyte release from the bone marrow and therefore prolongs the maturation time of circulating reticulocytes; this is likely the reason for findings showing a high reticulocyte count [18].…”
Section: Discussionmentioning
confidence: 99%
“…We extended the classical flow‐diffusion equation to take the biophysical effects of capillary transit time heterogeneity (CTH) into account and refer the reader to Jespersen and Østergaard22 and Østergaard et al 25. for details on the model and its application to brain and heart.…”
Section: Tissue Blood Flow Capillary Blood Flow Patterns and Oxygenmentioning
confidence: 99%
“…2 for the effects of reduced capillary volume and oxygen saturation) will reduce oxygen availability below the needs of normal tissue function. The figures for brain and heart were adapted from Jespersen and Østergaard22 and Østergaard et al 25…”
Section: Matching Blood Flow To the Metabolic Needs Of Kidney Heartmentioning
confidence: 99%